Design and development of biogas electrical power generation with an adaptive control mechanism for rural electrification - Vineeth Kumar Pothera Kariyat; Jijesh Jisha Janardhanan (Institute of Advanced Engineering and Science, 2023)
The primary goal of this research is to implement a model of biogas power generation unit used for rural electrification. A biogas reactor, a microturbine, a permanent magnet synchronous generator (PMSG), a rectifier, and a permanent magnet DC motor (PMDC) make up the proposed system. The biomass used to fuel the biogas reactor is typically derived from the surplus agricultural and animal waste found in rural areas. The operation of the biogas power system, design, and detailed mathematical modeling of each segment is described in this paper. In addition to that, an adaptive control mechanism is added to improve the system stability. The MATLAB/Simulink environment is used to develop the overall biogas fueled power system and thus obtained various parameters. The observation in the development has shown an improvement in biogas power generation unit’s suitability for standalone applications such as water pumping in rural area.